Survival analysis of palliative radiotherapy in patients with HER-2+ metastatic breast cancer - Li, Xueting; Zhong, Xiaorong; Xu, Hongyu; Wang, Jun; Liu, Xianguo; Wang, Yang; He, Liang; Ma, Jiayu; Li, Guanghua; Liu, Lei (Frontiers in Endocrinology, 2024)
Whether radiotherapy can improve the long-term survival of HER-2+ metastatic breast cancer remains unclear.We launched this study to explore the effect of HER-2+ metastatic breast cancer patients through anti-HER-2 targeted therapy + radiotherapy.March 2006 to September 2021 were retrospectively collected. Patients were divided into a radiotherapy group This is a provisional file, not the final typeset article (n=207) and a non-radiotherapy group (n=281) based on whether they received radiotherapy or not. 1: 1 propensity matching analysis was used to determine two groups of patients with similar baselines.Before matching, the radiotherapy group (n=207) had a median overall survival (mOS) of 51.7 months (48.8-63.8), which was superior to the non-radiotherapy group's (n=281) mOS of 33.9 months (27.9-39.9) (P < 0.0001). Moreover, the radiotherapy group exhibited better 1-year (94.6% vs 83.9%), 3-year (70.8% vs 45.5%), and 5-year (43.3% vs 25.0%) survival rates compared to the control group. Propensity score matching analysis identified 135 pairs of baseline-matched patients. In the matched groups, the mOS was 57.2 (44.5-69.8) months in the radiotherapy group (n=135) and 34.1 (27.5-40.6) months in the non-radiotherapy group (n=135), showing a statistically significant difference (P < 0.0001). Additionally, the radiotherapy group demonstrated 1-, 3-, and 5-year survival rates of 93.2%, 71.5%, and 46.9%, respectively, while those in the non-radiotherapy group were 89.4%, 45.8%, and 22.2%, respectively. Multivariate Cox analysis revealed that the presence of brain metastasis, liver metastasis, and radiotherapy were identified as independent predictive factors significantly associated with OS.In patients with HER-2 positive metastatic breast cancer, radiotherapy was associated with better survival benefits compared to those who did not receive radiotherapy.